Impact of strategic ambiguity tagline on billboard advertising on consumers attention - Nwankwo-Ojionu, Chimeziem E.; Adzharuddin, Nor Azura; Waheed, Moniza; Mohd Khir, Azlina (Online Journal of Communication and Media Technologies, 2021)
Using strategic ambiguity tagline paradigm, we demonstrated that the strategic ambiguity tagline influences consumer attention on billboard advertisement evaluation. Despite the exceptional influence of strategic ambiguity tagline on billboard advertisement evaluation, the concept of strategic ambiguity tagline as discursive resources remains poorly conceptualised by previous studies. An experimental study was conducted to investigate the underlying mechanisms and circumstances that influence the impact of strategic ambiguity tagline on consumers attention. Findings revealed that strategic ambiguity tagline has a significant influence on consumers attention. However, we further observed strong effects of attitude towards tagline ads, perception towards tagline ads and brand motives using tagline ads on consumer attention when exposed to the ads, which signify effectiveness of strategic ambiguity tagline on consumer’s attention. The theoretical and managerial implication are discussed.